Association between ACTN3 R577x and the physical performance of Chinese 13 to 15-year-old elite and sub-elite football players at different positions - Yang, Shidong; Lin, Wentao; Jia, Mengmeng; Chen, Haichun (Frontiers in Genetics, 2023)
The purpose of this study was to investigate the prevalence of ACTN3 polymorphisms in Chinese elite and sub-elite football players aged 13 to 15 years at different positions. Specifically we explored whether ACTN3 genotypes were linked with athletic performance of elite and sub-elite players at different positions. The RR genotype frequency of elite defenders (p = 0.018) and midfielders (p = 0.008) was significantly higher than that of sub-elite XX genotype in elite players. Furthermore, the R allele frequency of elite defenders (p = 0.003) and midfielders (p = 0.008) was significantly higher than that of sub-elite players. In all subjects, RR players performed faster and exhibited more explosive power than RX or XX players. RR, RX and XX elite players’ 20 m / 30 m sprint, 5×25-m repeated sprint ability (5×25 m RSA), and standing long jump were stronger than sub-elite players, but there was no significant different in aerobic endurance between elite and sub-elite players at different positions. In conclusion, there were significant differences in ACTN3 genotypes and alleles between elite and sub-elite players at different positions, and the RR genotype was significantly associated with power-related athletic performance in Chinese youth football players.